2014
DOI: 10.1007/s10815-014-0366-1
|View full text |Cite
|
Sign up to set email alerts
|

Using the Eeva Test™ adjunctively to traditional day 3 morphology is informative for consistent embryo assessment within a panel of embryologists with diverse experience

Abstract: The Eeva Test, an automated, time-lapse enabled prognostic test, used adjunctively with morphology, is informative in helping embryologists with various levels of experience select embryos with high developmental potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
(53 reference statements)
0
18
0
1
Order By: Relevance
“…First, the predictive capabilities of the early cell division timings P2 and P3 have been reported by multiple independent clinics and shown to be robust in different medium and culture conditions (19,26). Second, unlike other proposed embryo selection algorithms that have been reported from individual clinics, the algorithm that automatically classified embryos as having TL-high or TL-low potential was rigorously validated in a multicenter study (20,21) and shown to be generalizable to multiple clinics (23). Finally, in our experience, having automated image analysis and a prevalidated embryo classification model provides an efficient option for IVF laboratories to take full advantage of the benefits of time-lapse technology.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…First, the predictive capabilities of the early cell division timings P2 and P3 have been reported by multiple independent clinics and shown to be robust in different medium and culture conditions (19,26). Second, unlike other proposed embryo selection algorithms that have been reported from individual clinics, the algorithm that automatically classified embryos as having TL-high or TL-low potential was rigorously validated in a multicenter study (20,21) and shown to be generalizable to multiple clinics (23). Finally, in our experience, having automated image analysis and a prevalidated embryo classification model provides an efficient option for IVF laboratories to take full advantage of the benefits of time-lapse technology.…”
Section: Figurementioning
confidence: 99%
“…Conaghan et al demonstrated that, used together with traditional morphology, TL-test results significantly improved three embryologists' abilities to identify cleavage-stage embryos that developed into blastocysts (20). Extending these results, Diamond et al reported consistent improvement in embryo selection ability for five additional embryologists who had diverse backgrounds and levels of embryology experience and who were not involved in the development or original validation of the TL-test (21). The results of Diamond et al formed the basis for a de novo clearance by the FDA, which in 2014 cleared the Eeva TL-test as a first time-lapse-based prognostic test for aiding embryo selection.…”
mentioning
confidence: 98%
“…The use of Eeva® in addition with standard morphology assessment has been compared with standard morphology assessment in few randomized clinical trials with different conclusions. On one hand Eeva® seemed to give objective information for helping embryologists with various levels of experience to choose the best embryo to transfer in a double-blinded multi-center study with 54 patients undergoing blastocyst transfer (Diamond et al, 2015), on the other hand, an observational prospective two-center study did not demonstrate any improvement in cycle outcome when using Eeva® (Kieslinger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The idea of using AI to aid decision-making for infertility treatment has been developed over many years, with an early proposal by Schild et al [62]. Despite increasing interest, AI is not routinely used by fertility clinics for making treatment decisions, but is starting to be used in infertility laboratories, with a number of tools for embryo monitoring and selection [63][64][65][66][67][68][69] currently available for objective judgment and choice of gametes and embryos using AI-picture analytics and decision-supporting algorithms [70]. The aim of these tools is to provide an objective recommendation for embryologists, enabling the standardization of treatment across different centers by removing operator variability/subjectivity.…”
Section: Future Perspectivesmentioning
confidence: 99%